Malocclusion and articulation disorders in mouth breathing children from public schools in Santa Maria, Rio Grande do Sul - Ana Maria Toniolo da Silva; Angela Ruviaro Busanello; Clarissa Flores Oliveira (Faculdade São Leopoldo Mandic, 2008)
Objective: To verify the occurrence and types of malocclusion and articulation disorders in mouth breathing children at public schools.Methods: An evaluation was made of 219 children of both genders, between 5 and 12 years of age, attending two public schools in the city of Santa Maria, Rio Grande do Sul, Brazil; with 121 mouth breather children being selected for this study. Orthodontic and phonoaudiological evaluation were made to verify the breathing mode and presence or absence of malocclusion and articulation disorders.Results: It was observed that 100% of the mouth breather children presented malocclusion, 49.60% being Angle's Class II, 48.76% ClassI and 1.65% Class III. It was also verified that 18.2% of the mouth breather children presented articulation disturbance. Conclusion: All mouth breathing children presented some type of malocclusion, the majority being Angle's Class II, followed by Class I. The articulation disorders most frequently observed was anterior lisping.